العلاقة بين الذكاء الوجداني واتخاذ القرار لدى طلاب المرحلة الثانوية بمكة المكرمة - العتيبي، محمد عبيد الله Alotaibi, Mohammed Obaidullah; أبو لطيفة، لؤي حسن محمد Abu Latifah, Luay Hasan Mohammed (جامعة أسيوط - كلية التربية, 2019)
The Present Study Aimed to Identify The Level of Emotional Intelligence and Decision Making For Secondary Stage Students, and Discovering of The Differences Between Individuals Sample Study on Emotional Intelligence and Decision-Making According to the Different Grade , and Finally The study Aims to Uncover the Relationship Between Emotional Intelligence and Decision-Making among A Sample Secondary Stage Students, The Current Study was Conducted on Sample of (500 , Male) for Secondary Stage Students They were Randomly Chosen ، to Achieve The Objectives of The Study, The Researcher Used A Scale, scale of Emotional Intelligence, which was Prepared by Alwan (2012) , and Scale of Decision-Making, which was Prepared by Abdoun (1979),Using The Appropriate Statistical Methods, the study reached the following - Level emotional intelligence and Level Decision-Making for Secondary Stage Students Low than Average ,There are Differences Between Individuals Sample Study on Emotional Intelligence and Decision-Making According to the Different Grade , for Third Graders. The study Confirmed a Relationship Between Emotional Intelligence and Decision-Making among A Sample Secondary Stage Students ,The Researcher Recommended The Need for Educational Attention to The Concept of Emotional Intelligence ,Through Guidance and Counseling , so That We Can Raise Our Children from Secondary School Students , to Be Able to Make Important Decisions , With Which it is Possible to Achieve A Better Future for Them, God Willing .
هدفت الدراسة الحالية التعرف على درجة الذكاء الوجداني واتخاذ القرار لدى أفراد عينة الدراسة من طلبة المرحلة الثانوية، وكذلك الكشف عن اتجاه الفروق بين الأفراد عينة الدراسة في الذكاء الوجداني واتخاذ القرار وذلك وفقاً لاختلاف الصف الدراسي، والتوصل إلى نوع العلاقة الارتباطية بين الذكاء الوجداني واتخاذ القرار لدي الأفراد عينة الدراسة من طلبة المرحلة الثانوية بمكة المكرمة، وقد تكونت عينة الدراسة من (500) طالب من طلاب المرحلة الثانوية الذكور بمكة المكرمة تم اختيارهم بطريقة عشوائية، ولتحقيق أهداف الدراسة استخدم الباحث مقياس الذكاء الوجداني إعداد: العلوان (2010)، ومقياس اتخاذ القرار إعداد: عبدون (1979)، وباستخدام الأساليب الاحصائية المناسبة توصلت نتائج الدراسة إلى أن مستوي الذكاء الوجداني ومستوي اتخاذ القرار لدي أفراد عينة الدراسة من طلبة المرحلة الثانوية بمكة المكرمة أقل من المتوسط، كما أنه توجد فروق بين طلاب المرحلة الثانوية في درجة الذكاء الوجداني واتخاذ القرار وفقا لاختلاف مستوي الصف الدراسي وذلك لصالح طلاب الصف الثالث الثانوي، ولقد أثبتت النتائج وجود علاقة ارتباطية بين الذكاء الوجداني واتخاذ القرار لدي طلبة المرحلة الثانوية بمكة المكرمة، وفى النهاية أوصي الباحث بضرورة الاهتمام التربوي بمفهوم الذكاء الوجداني وذلك عن طريق التوجيه والإرشاد النفسي حتي يتسنى لنا تربية أبنائنا من طلاب المرحلة الثانوية ليصبحوا قادرين على اتخاذ القرارات الهامة والتي معها يمكن تحقيق مستقبل أفضل لهم بإذن الله.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- طرق التدريس -- التعليم الثانوي -- طلاب المرحلة الثانوية -- الصحة النفسية -- الرعاية الإجتماعية -- المقاييس والإختبارات التربوية -- الذكاء الوجداني -- مكة المكرمة -- السعودية -- المجتمع السعودي -- مستخلصات الأبحاث -- الترجمة -- اللغات الأجنبية